Feasibility of reverberant shear wave elastography for in vivo assessment of skeletal muscle viscoelasticity - MacHado, E.; Romero Gutierrez, S.E.; Flores, G.; Castañeda, B. (IEEE Computer Society, 2020)
Quantifying the local stiffness of muscular tissue can be a useful tool for the improvement of diagnosis, treatment or monitoring of muscle abnormality-related diseases. Shear wave elastography techniques provide information about tissue stiffness by measuring the shear wave speed (SWS). Recently, a new framework involving the generation of a reverberant shear wave field that propagates in all directions within the medium was proposed. The aim of this study is to evaluate the feasibility of Reverberant Shear Wave Elastography (R-SWE) for the in vivo assessment of the viscoelastic properties of skeletal muscle, using the biceps brachii. Four experiments were performed at a vibration frequency range between 200-300 Hz in steps of 50 Hz, with the ultrasound transducer placed along the muscle fibers in both relaxed and contracted (MVC) states. The estimation of the SWS and a dispersion analysis using the Kelvin-Voigt Fractional Derivative (KVFD) model were carried out in order to assess the viscoelastic properties of the muscular tissue. Preliminary results show that R-SWE is feasible to use for the in vivo assessment of skeletal muscle by using a multifrequency approach. The viscoelastic parameters obtained by the KVFD curve-fitting and the dispersion analysis showed the expected differences between the relaxed and MVC states (i.e. a significant difference between the coefficient of viscosity and the dispersion rate of change). The SWS estimation also showed differences between the two states (e.g. a difference in SWS values of 35.52% at 300 Hz).
Keywords: Elastography; Viscoelasticity; Magnetic resonance elastography; Computer science; Shear (geology); Skeletal muscle; Stiffness; Biomedical engineering; In vivo; Acoustics; Artificial intelligence; Physics; Ultrasound; Materials science; Anatomy; Medicine; Biology; Composite material; https://purl.org/pe-repo/ocde/ford#2.06.00